2019
DOI: 10.1002/mnfr.201900065
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Manganese Exposure in the Adult Population in Germany—What Does it Mean in Relation to Health Risks?

Abstract: Manganese is both an essential nutrient and a potential neurotoxicant. Therefore, the question arises whether the dietary manganese intake in the German population is on the low or high side. Results from a pilot total diet study in Germany presented here reveal that the average dietary manganese intake in the general population in Germany aged 14–80 years is about 2.8 mg day−1 for a person of 70 kg body weight. This exposure level is within the intake range of 2–5 mg per person and day as recommended by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 215 publications
(294 reference statements)
3
19
0
Order By: Relevance
“…Based on the biological justification of sex differences in manganese metabolism [5,19] the analyses of the manganese/type 2 diabetes were presented for men and women separately. Sexspecific daily manganese intakes were divided into quartiles and the sex-specific age-adjusted trends of participants' characteristics across the increasing quartiles of manganese intake were tested by logistic regression for proportions and linear regression for mean values.…”
Section: 3statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the biological justification of sex differences in manganese metabolism [5,19] the analyses of the manganese/type 2 diabetes were presented for men and women separately. Sexspecific daily manganese intakes were divided into quartiles and the sex-specific age-adjusted trends of participants' characteristics across the increasing quartiles of manganese intake were tested by logistic regression for proportions and linear regression for mean values.…”
Section: 3statistical Analysesmentioning
confidence: 99%
“…Therefore, we aimed to examine the association between dietary manganese and risk of type 2 diabetes using the data of the Japan Collaborative Cohort (JACC) study. Because there was an evidence of sex differences in the manganese absorption rate, manganese blood levels and biological half-time of manganese, in favor of women than men [19], we hypothesized that dietary manganese intake could be associated with the reduced risk of type 2 diabetes, especially among women.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that DHA and CLA exerted biological effects through active transport absorption mediated by membrane transporters (de Gaetano et al., 2015; Wong et al., 2016). Increasing intake of DHA and CLA has been recommended by dietary guidelines in the United States, Germany, and Brazil (Dwyer, 2012; Sachse et al., 2019; Sarma et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EFSA has proposed an adequate daily intake of 3 mg/day for adults [31]. The average dietary exposure amounts to 2.8 mg for a 70 kg person [32]. Intoxications with manganese cause symptoms similar to those of Parkinson's disease.…”
Section: Release Of Elements From Elastomers Into Food Simulantsmentioning
confidence: 99%